Pedagogical Press of Ukraine: Model of Gender Issue Explicitness - Susanna Emirilyasova (Pedagogical Discourse, 2013)
The article is devoted to the pedagogical press in Ukraine that performs as a translator of gender pedagogy ideas. The usage of the gender component in the pedagogical publications is offered to be identified by means of explicitness of gender issues consisting of nine basic parameters : androcentric/ gender marked title of pedagogical publication, gender of addressee of the pedagogical publication; androcentric/ gender marked headlines of the pedagogical articles, the ratio of author articles on the basis of sex; the names of scientists (pedagogues, philosophers, psychologists), that are mentioned by the authors in the articles; the names of scientists specializing in the field of gender studies mentioned by the authors in articles; terminology of publications, the presence of the androcentric/ gender- marked wordsin the text of the publication, the popularization in the pedagogical publication of contexts transmitting/ transforming gender stereotypes.